In vitro establishment of Salvia hispanica L. plants and callus - Patricia L Marconi; María C López; Jürgen De Meester; Celia Bovjin; María A Alvarez (Biotecnología Vegetal, 2013)
We have optimized the culture conditions for the initiation and maintenance of Salvia hispanica L. (Chia) plant and callus cultures. Stems section were the best explant source for starting in vitro cultures. Both IAA and NAA, at all the concentration tested with or without the addition of citokinines, have induced the development of adventitious roots both in darkness as in light. In darkness, 2,4-D (2.25 mM) has induced the development of S. hispanica embryogenic tissues and in light promoted the initiation and establishment of green, and fast-growing calli that lost their friability with time. When subcultured to MS culture media with NAA:kin (0.54 mM:0.46 mM) or Picloram (1.72 mM, 3.43 mM) as plant growth regulators, calli maintained friability for two years in culture. It was possible to detect fatty acid content in the calli obtained but the values remained significant lower than those of seeds.